Safe use of Peripherally Inserted Central Catheters for chemotherapy of solid malignancies in adult patients: A 1-year monocentric, prospectively-assessed, unselected cohort of 482 patients. Issue 6 (November 2021) - Piredda, Alessio; Radice, Davide; Zencovich, Claudia; Cerri, Martina; Aventino, Lucia; Naccarato, Francesco; Magon, Giorgio; Biffi, Roberto
Introduction: Aim of this study was to analyze the overall complication and failure rates of Peripherally Inserted Central Catheters (PICCs), in a 1-year consecutive unselected cohort of 482 adult patients, affected by non-hematological malignancies undergoing chemotherapy. Methods: Adult outpatients (aged 18–75 years), with an Eastern Cooperative Oncology Group (ECOG) performance status of 0–2, bearing solid tumors and candidates for intravenous chemotherapy were eligible for the study. Exclusion criteria were active infections, coagulopathy (defined as platelet count <50, 000/μL and/or prothrombin time more than 18 s), life expectancy <6 months, or inability to give written informed consent. Devices were all implanted in an outpatients' hospital facility, following predefined evidence-based institutional guidelines and protocols by a PICC-dedicated team at the European Institute of Oncology in Milan, Italy, during the 12-month period from January 1 to December 31, 2019. Results: Five-hundred PICCs were implanted in a cohort of 482 patients during the time interval of this study. Thirty devices were overall removed (6.2%), 23 as a consequence of a complication occurred, and seven inadvertently. The inserted PICCs accounted for a total of 49, 718 catheter days in situ, median duration was 85.5 days [interquartile range (IQR): 56–146]. Overall there were 42 (8.7%) complications, corresponding to 0.84 catheter-adverse events (CAE)/1000 PICC-days (95% CI: 0.61–1.14). There were N = 13 (2.7%) thromboses, N = 11 (2.3%) irreversible occlusions, N = 7 (1.5%) accidental removals, N = 5 (1.0%) infections [two Catheter Related Blood Stream Infection (CRBSI) and three exit site/local infection], N = 3 (0.6%) ruptures and N = 3 (0.6%) primary or secondary malpositions. Conclusion: This large prospective study supports the increasing use of PICCs in adult oncology outpatients treated in specialized centers with chemotherapy for non-hematological malignancies. In this clinical setting, PICC failure occurred in 6% only of the inserted devices.